Strategi promosi perpustakaan: Film animasi sebagai media edukasi bagi pemustaka - Atiqa Nur Latifa Hanum (Jurnal Informatio, 2021)
The animated series of Upin and Ipin has a unique series entitled “Aku Sebuah Buku”. It show a library representation of the local culture which is packaged with artistic living painting to attract and ease the understanding the meaning of the symbols displayed. The popularity of libraries has not increased until now, threfore a promotional strategy is needed as an effort to educate users to increase popularity. This study used a narrative method with a qualitative approach to find out the signs and markers displayed in the series. The respondents were 11 childrens who watched this film. The data analysis was carried out in three stages, namely data reduction, data presentation, and ideology interpreted by respondents and experts show that this film is building a positive image of a library for the open-minded society who has the biggest interest in books. It can be concluded that animation film has succesfull and become reliable as an educational medium alternative ineffective library promotion strategy in informing and persuading shildren to visit the library which can be seen from their interest and motivation to visit the library and oing the same things after watching the animated film of Upin and Ipin.